Pembuatan Tepung Gel Lidah Buaya dengan Alat Pengering Spray Dryer - Ronny Kurniawan; Salafudin Salafudin; Ilham Husnul Abid (Seminar Nasional Teknik Kimia Kejuangan, 2016)
Aloe vera (aloe vera) had the potential to be developed as a medicinal plant and industrial raw materials. The most important part that commonly used in the processing of aloe vera is it gel, but it has highly water contain and makes aloe vera gel easily damaged and had a low durability against microorganism invades. The results of preliminary test, the water content in the aloe verathat we use is98,66% - 99,49%, therefore it is necessary for processing into another form with less water contains, that was into flour form. Besides to preserve, this treatment also to increase the selling price of aloe verawhen sold in the form of flour. Aloe vera in the form of flour has several advantages, that is nutritional content is not changed and easy to stored and transported. The advantages of this flour in industry are more practical, stables and not easily damaged. There are a lot of processes to preserve and facilitate the processing of aloe vera, one that is by drying. Among the dryer that can be used in processing aloe vera into powder is using spray dryer. The advantages of this dryer is the contact process was not require a long time. The drying process is performed continuously with the parameters of chamber size, nozzle type (fluid nozzle), the rate of drying air (0,8 m3/min) and the variable are drying air temperature of 60°C, 90°C, and 12°C, feed rate of 2,9 mL/min, 6,2 mL/min, and 13mL/min. This drying process taken places in three stages: the initial stage, drying stages and analysis phase. In this study, we obtained that the best conditions are at temperature of 170 °C with feed flow rate of 2.9 mL/min, a feed moisture content of 99.4%, the water content of aloe vera gel powder at 9.16%, with color powder aloe gel cream pale, pH of 5, microorganism content of 5,33.109sel/g, vitamine C of 114,15 mg/100g sample,and a yield of 0.15%.